HUBUNGAN ANTARA UMUR DENGAN CALVING INTERVAL, DAYS OPEN, DAN SERVICE PER CONSEPTION SAPIFRIESIAN HOLSTEIN (FH) - Ananda, Hanifah Muslimah; Wurlina, Wurlina; Hidajati, Nove; Hariadi, Mas'ud; Samik, Abdul; Restiadi, Tjuk Imam (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of this research was to know the relationship between age with calving inteval (CI), days open (DO), and service per conception (S/C) in Friesian Holstein dairy cattle (FH). The research was started on Desember 2017 to January 2018 in PT. Greenfields Indonesia partnerships, KecamatanWagir Kabupaten Malang. The materials of the search used were 100 heads of dairy cattle which had at least two times of parturition. The method used in this research was a survey and data collection. The data were obtained from the records of reproduction. Data analysis was multiple linear regression using SPSS software 21.0 version. The results showed that the values of CI (434,9±58,9 days, 449,4±66,2 days, and 431,8±59,2 days), DO (218,9±58,7 days, 218,9±58,7 days, dan 217,6±54,1 days), dan S/C (3,2±1,8 times, 4,3±1,9 times, 2,6±1,1 times) for the ages of 4, 5, 6. The relationship between age with CI and DO were not significant (P>0,05), but the relationship between age with S/C was significant (P<0,05). The value of S/C increased on dairy cattle at age of 4 to 5 years and started to decreased at the age of 6 years.